2021
DOI: 10.1111/jfpp.15391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and digestion properties of corn starch esterified by l ‐malic acid

Abstract: Starch is abundant in nature and easy to obtain. Many of its unique physical and chemical properties are widely used in food and other industries (Azeh et al., 2018;Singh et al., 2003). However, most of the native starch itself does not have the properties of being directly utilized. After modification, the starch properties are improved to meet the requirements of multilevel processing (Haq et al., 2019;Kaur et al., 2012). Starch is a storage polysaccharide and one of the main components of corn. It is about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
2
1
0
Order By: Relevance
“…The results for SDexF obtained on a semi-industrial scale were consistent with those obtained for SDexF prepared on a laboratory scale [22]. In studies by other authors, starches modified by acids and enzymes also showed lower pasting parameters compared to native starches [62,63].…”
Section: Pasting Properties Of Sdexfsupporting
confidence: 86%
See 1 more Smart Citation
“…The results for SDexF obtained on a semi-industrial scale were consistent with those obtained for SDexF prepared on a laboratory scale [22]. In studies by other authors, starches modified by acids and enzymes also showed lower pasting parameters compared to native starches [62,63].…”
Section: Pasting Properties Of Sdexfsupporting
confidence: 86%
“…The results for SDexF obtained on a semi-industrial scale were consistent with those obtained for SDexF prepared on a laboratory scale [22]. In studies by other authors, starches modified by acids and enzymes also showed lower pasting parameters compared to native starches [62,63]. Comparing the pasting property curves of starch and SDexF, one of the SDexF batch curves is presented with a potato starch curve in Figure 4.…”
Section: Pasting Properties Of Sdexfsupporting
confidence: 85%
“…Esterified starch produced by organic acid modification is commonly considered as resistant starch, like citrate starch ester, malate starch ester, acetate starch ester, etc. [ 12 ]. The hydroxyl group on the glucose unit of esterified starch is esterified, resulting in a great change in the properties of natural starch, which is widely used in food, pharmaceutical, textile, paper and other industries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%